Einbruchsdelikte Strafzumessung, Rückfälligkeit und kriminelle Karrieren - Griegel, Ramona (Universitätsverlag Göttingen, 2021)
Burglary offenses, especially domestic burglaries, have increasingly been the focus of public interest in recent years. This area of crime is essential for the public's sense of security and thus also for crime policy. The tightening of penalties for domestic burglary enacted by the legislature in 2017 has been the subject of widespread discussion in criminal policy and criminal law dogmatics. This study addresses the offense area of burglary from an empirical perspective, the sanctioning of offenders as well as their criminal history and recidivism by evaluating a nationwide dataset from the Federal Central Register. Using the underlying data material, the criminal careers of burglars are also analyzed prospectively over a nine-year recidivism period and - if no redemptions were made - retrospectively over an indefinite period.